Magnetic wastewater treatment system by using magnetic polyamide epichlorohydrin as adsorbents - Mohd Hamdan Dasuki, Hamid (2006)
The main objectives of this study are to reduce concentration of lead in wastewater and to fabricate a new system based on magnetic and adsorption concept. In this study, prototype of wastewater system is fabricated. This prototype used a hardware components and electrical components. The system completed with existences of adsorbent. The magnetic polyamide epichlorohydrin (MPE) is used as adsorbents and it is produced by reaction of major chemicals; epichlorohydrin, ammonia solution, polyethlenemine and activated ferrite. This adsorbents assumed could reduced the lead concentration in wastewater. The parameter in this study is duration of cycle. A result conducted base on 5 min of cycle, 10 min of cycle, 15 min of cycle, 20 min of cycle, 25 min of cycle and 30 min of cycle. Based on the result of experiment, the concentration of lead reduced about 82% of the concentration before. This experiment concludes that magnetic polyamide epichlorohydrin is suitable to reduce lead.